-(5x-5)-(6x-5)+9=-9(x-1)-(5x+8)+3

Simple and best practice solution for -(5x-5)-(6x-5)+9=-9(x-1)-(5x+8)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(5x-5)-(6x-5)+9=-9(x-1)-(5x+8)+3 equation:


Simplifying
-1(5x + -5) + -1(6x + -5) + 9 = -9(x + -1) + -1(5x + 8) + 3

Reorder the terms:
-1(-5 + 5x) + -1(6x + -5) + 9 = -9(x + -1) + -1(5x + 8) + 3
(-5 * -1 + 5x * -1) + -1(6x + -5) + 9 = -9(x + -1) + -1(5x + 8) + 3
(5 + -5x) + -1(6x + -5) + 9 = -9(x + -1) + -1(5x + 8) + 3

Reorder the terms:
5 + -5x + -1(-5 + 6x) + 9 = -9(x + -1) + -1(5x + 8) + 3
5 + -5x + (-5 * -1 + 6x * -1) + 9 = -9(x + -1) + -1(5x + 8) + 3
5 + -5x + (5 + -6x) + 9 = -9(x + -1) + -1(5x + 8) + 3

Reorder the terms:
5 + 5 + 9 + -5x + -6x = -9(x + -1) + -1(5x + 8) + 3

Combine like terms: 5 + 5 = 10
10 + 9 + -5x + -6x = -9(x + -1) + -1(5x + 8) + 3

Combine like terms: 10 + 9 = 19
19 + -5x + -6x = -9(x + -1) + -1(5x + 8) + 3

Combine like terms: -5x + -6x = -11x
19 + -11x = -9(x + -1) + -1(5x + 8) + 3

Reorder the terms:
19 + -11x = -9(-1 + x) + -1(5x + 8) + 3
19 + -11x = (-1 * -9 + x * -9) + -1(5x + 8) + 3
19 + -11x = (9 + -9x) + -1(5x + 8) + 3

Reorder the terms:
19 + -11x = 9 + -9x + -1(8 + 5x) + 3
19 + -11x = 9 + -9x + (8 * -1 + 5x * -1) + 3
19 + -11x = 9 + -9x + (-8 + -5x) + 3

Reorder the terms:
19 + -11x = 9 + -8 + 3 + -9x + -5x

Combine like terms: 9 + -8 = 1
19 + -11x = 1 + 3 + -9x + -5x

Combine like terms: 1 + 3 = 4
19 + -11x = 4 + -9x + -5x

Combine like terms: -9x + -5x = -14x
19 + -11x = 4 + -14x

Solving
19 + -11x = 4 + -14x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '14x' to each side of the equation.
19 + -11x + 14x = 4 + -14x + 14x

Combine like terms: -11x + 14x = 3x
19 + 3x = 4 + -14x + 14x

Combine like terms: -14x + 14x = 0
19 + 3x = 4 + 0
19 + 3x = 4

Add '-19' to each side of the equation.
19 + -19 + 3x = 4 + -19

Combine like terms: 19 + -19 = 0
0 + 3x = 4 + -19
3x = 4 + -19

Combine like terms: 4 + -19 = -15
3x = -15

Divide each side by '3'.
x = -5

Simplifying
x = -5

See similar equations:

| 2+4X=4-(x-3) | | 2[m+1]=16 | | =364x | | 9e+4e+7f+2f= | | 6x^2+18xy^2-24xy= | | 25x=150-65 | | 13+2[5c-2]=29 | | 14+3x=3+5x+4 | | x^3+10x^2+33x+36=0 | | 2x^2+2y^2+2xy+10x+2y+14=0 | | 8x-(1-5x)=17+7x | | 2(x+10)=7(x+2)-4x | | f(x)=x^3+10x^2+33x+36 | | 105-x-40+3x=150 | | 7c-4=7 | | 3x+12=(x+1) | | 105-35-40+60=150 | | (x+1)(x-6)=(x+5)(x-2) | | 4x-2x=3(x-3) | | 16x^3-28x^2+4x=-8x | | 7x-11=5(x-2)+2x | | x^3+2x^2=80x | | 7(3n-3)=(7n+7)+4 | | 5x+7=.5(10x+12) | | 5x+7=1.2(10x+12) | | 35(3-x)-20(2-3x)=150 | | 3=-3/5(m-9) | | 3+35x=15x+7 | | 2c-6=4c+4 | | x-(-8)=-32 | | 4v+2-2(-8v-1)=2(v-3) | | X(.75)=3 |

Equations solver categories